EXPLORING STUDENTS’ PUBLIC SPEAKING SKILLS THROUGH BUSINESS MEETING SIMULATION - Pusparini, Diah Anita; Suryatiningsih, Ninik (Universitas Lambung Mangkurat, 2023)
n today’s sophisticated era, public speaking has become a crucial skill for effective communicating in formal meetings. Equipping students with the confidence to address audience is essential in speaking classes. Hence, simulation practices, like Business Meeting presentation, are employed to enhance their public speaking abilities. This descriptive qualitative study utilized a case study design, collecting the data through observation, questionnaires, and documentation from 33 students in Public Speaking class. The students’ Business Meeting presentations were observed and recorded, and supplemented with insights Google form questionnaire regarding their knowledge, preparation, difficulties, and perceived benefits during the presentations. The finding reveled students’ enthusiasm for Business Meeting presentation as a form of Public Speaking practice. While not all students achieved a high level a proficiency, most demonstrated commendable presentations when adequately prepared. Despite experiencing nervousness and lack of confidence while speaking to the public, they effectively overcome these challenges through meticulous preparation. Overall, the Business Meeting simulation proved beneficial in fostering students’ public speaking skills, emphasizing the importance of preparation and creativity in effective preparations. This study encouraged further exploration of innovative techniques to enhance public speaking education.